2018
DOI: 10.1016/s1470-2045(18)30294-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of response markers to predict survival and pleurodesis success in patients with malignant pleural effusion (PROMISE): a multicohort analysis

Abstract: European Respiratory Society, Medical Research Funding-University of Oxford, Slater & Gordon Research Fund, and Oxfordshire Health Services Research Committee Research Grants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
3
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 27 publications
5
95
3
4
Order By: Relevance
“…However, a recent study suggested that it underestimates the prognosis in patients with MPE caused by lung adenocarcinoma . The recently published PROMISE score system includes a clinical score method and a biological score method, which is a clinical score plus tissue inhibitor of metalloproteinases 1 (TIMP1). However, this system can only predict the 3‐month mortality, and adding TIMP1 to the score system only contributed very modest effects, which limited its clinical value .…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study suggested that it underestimates the prognosis in patients with MPE caused by lung adenocarcinoma . The recently published PROMISE score system includes a clinical score method and a biological score method, which is a clinical score plus tissue inhibitor of metalloproteinases 1 (TIMP1). However, this system can only predict the 3‐month mortality, and adding TIMP1 to the score system only contributed very modest effects, which limited its clinical value .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, all eight biomarkers examined in the prediction of pleurodesis outcomes were unsuccessful, including tumor necrosis factor (TNF) α, TNFβ, interleukin 6, and fibroblast growth factor 2. 3 Although unsuccessful in predicting pleurodesis outcome in this instance, potential has been shown with the development of a prognostic survival score using biomarkers and further investigation is warranted. 3.…”
Section: Sonographic Pleurodesis: Prediction Unexpandable Lungmentioning
confidence: 98%
“…1,2 This figure is influenced by a number of factors, including performance status and tumor type, but can be risk stratified to predict prognosis using a number of tools including the LENT score and the more recently published and more accurate PROMISE tool. 2,3 Interventions available to patients and clinicians in the management of MPE include therapeutic pleural aspiration, indwelling pleural catheters (IPCs), or talc pleurodesis either using talc slurry instilled via an intercostal chest drain or talc poudrage administered during thoracoscopy. Each management option has various indications, roles and sequelae, and is dependent on multiple factors including availability, the underlying pathophysiology and patient choice among others.…”
Section: Overall Approach and Patient Perspectivementioning
confidence: 99%
“…46,71,72 The PROMISE score (►Table 3) helped predict survival that appeared to perform better than the LENTscore. 73 Pleurodesis success rates are also affected by tumor types, where those with mesothelioma and lung cancer-associated MPE failing more often when compared with MPE secondary to breast cancer (53 and 58% vs. 75%). 74 This is postulated to be related to a lower tumor load among the latter MPEs.…”
Section: Malignant Pleural Effusionsmentioning
confidence: 99%